2014
DOI: 10.1111/dme.12540
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in South Asians

Abstract: Economic, dietary and other lifestyle transitions have been occurring rapidly in most South Asian countries, making their populations more vulnerable to developing Type 2 diabetes and cardiovascular diseases. Recent data show an increasing prevalence of Type 2 diabetes in urban areas as well as in semi-urban and rural areas, inclusive of people belonging to middle and low socio-economic strata. Prime determinants for Type 2 diabetes in South Asians include physical inactivity, imbalanced diets, abdominal obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 43 publications
2
73
0
Order By: Relevance
“…However, true nationally representative data, which include urban and rural prevalence, are lacking from most of these countries, including India. South Asian populations also have a high prevalence of prediabetes and a more rapid progression to diabetes (13). This is highlighted by a recent study that reported a diabetes incidence of 22.2 per 1,000 person-years and that 59% of those with prediabetes converted to diabetes after a follow-up of 9.1 years (52).…”
Section: South Asiamentioning
confidence: 99%
See 3 more Smart Citations
“…However, true nationally representative data, which include urban and rural prevalence, are lacking from most of these countries, including India. South Asian populations also have a high prevalence of prediabetes and a more rapid progression to diabetes (13). This is highlighted by a recent study that reported a diabetes incidence of 22.2 per 1,000 person-years and that 59% of those with prediabetes converted to diabetes after a follow-up of 9.1 years (52).…”
Section: South Asiamentioning
confidence: 99%
“…Studies from other parts of India have also shown increases in diabetes prevalence (13,46). India is the largest country in the region and has more than 65.1 million people with diabetes, occupying the second position next to China in the IDF global list of top 10 countries for people with diabetes.…”
Section: South Asiamentioning
confidence: 99%
See 2 more Smart Citations
“…Our results demonstrated that 44.44% of those with more than 20 years of service were overweight; accordingly, this sector of society should be accorded pride of place in executive plans for reducing CVD risk factors (32). Also, reports that type 2 diabetes affects South Asians a decade earlier necessitates that due attention be paid to effective national diabetes control programs in each South Asian country (33).…”
Section: Discussionmentioning
confidence: 99%